HUBUNGAN ANTARA CITRA TUBUH DENGAN SELF COMPASSION PADA SISWA - Nur Azizah; Agung Nugraha (Journal of Innovative Counseling : Theory, Practice, and Research, 2021)
This research is motivated by a growing phenomenon among adolescents related to negative body image. The purpose of this study was to determine the correlation between body image and self-compassion in SMA Negeri 7 Tasikmalaya students. This study uses a quantitative descriptive approach with a correlational design. The sample in this study was students of SMA Negeri 7 Tasikmalaya grades X and XI, totaling 764 populations with 242 samples. The sample in this study was taken using a random sampling technique, namely random sampling from the population without looking at the strata in the population itself. The data analysis technique used in this study was that there was a negative relationship with a low category of -0.361 between negative body image and self-compassion. Based on the research results, it is necessary to develop guidance and counseling interventions to reduce negative body image to positive body image and increase self-compassion by using the Mindfulness Based Cognitive Therapy (MBCT) counseling technique.